Political Engineering for Women in Indonesian Governance - Vermonte, Philips Jusario (Yayasan Jurnal Perempuan, 2014)
The rising number of women in parliament is a vital entry point to involve more women politics. This factor opens discourse, engagement and active participation that can elevate women’s political bargain in negotiation room. It is in the long run will affect the embodiment of critical mass which is believed to increase factor of women’s representation in policies decision. Mainstreaming gender in governance shall be supported by political engineering, institutional setting, roles of the game, and an open and democratic system. Democratic political setting is the pre-requisite to create equal representation and participation for women and other minorities group in governance politics.